2020
DOI: 10.1109/tgrs.2020.2968029
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Daily Wildfire Activity Using Poisson Regression

Abstract: Wildfires and their emissions reduce air quality in many regions of the world, contributing to thousands of premature deaths each year. Smoke forecasting systems have the potential to improve health outcomes by providing future estimates of surface aerosol concentrations (and health hazards) over a period of several days. In most operational smoke forecasting systems, fire emissions are assumed to remain constant during the duration of the weather forecast and are initialized using satellite observations. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
(43 reference statements)
0
12
0
1
Order By: Relevance
“…The outcome is an %31 improvement above climatology. Graff et al [10] used PR to forecast daily wildfire activities. The results show that regression models significantly outperform traditional persistencebased models used in operational smoke forecasting applications at both the cell and regional levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcome is an %31 improvement above climatology. Graff et al [10] used PR to forecast daily wildfire activities. The results show that regression models significantly outperform traditional persistencebased models used in operational smoke forecasting applications at both the cell and regional levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…N ATURAL disasters, such as earthquakes, floods and tsunami, can cause serious social and economic devastation. When a natural disaster strikes, accurate and immediate responses are required in Humanitarian Assistance and Disaster Response (HADR) for saving thousands of lives [1], [2], [3], [4]. Before these responses, rescue planning and preparations are conducted based on damage analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach is widely accepted by the modeling community, it has limitations for cases where fires exhibit significant day-to-day variations in the burned area or when the fire emissions do not conform to a typical diel pattern. Recent work by Graff et al (2020) highlighted the limitations of assuming unchanged diurnal patterns and showed that regression models accounting for weather-driven changes in fire activity often perform better. For plume rises, most AQ models parameterize the smoldering fraction and calculate plume-top height using methods developed for point-source modeling (e.g., industrial facilities).…”
Section: Introductionmentioning
confidence: 99%